(3faM GdWjH ef ZUf GdCfOdS GdQWjH hPcQ hRjQgG dSGf GdOjf Hf GdNWjHs - (3GdebQj , CMeO Hf eMeO Hf CMeO Hf jMji GdJdeSGfj, CHh GdYHGS,J (B1041 (3g` s
(3ChdgG (B:s
(3JHOC HGdHGH GdSGOS ef GdbSe GdChd ai PcQ HYV GdhGaOjf Ydi GdCfOdS ef Cgd GdeTQb s
(3BNQgG (B:s
(3JfJgi HBNQ GdHGH GdKGfj ef GdbSe GdKGfj , hgh GdNGU fTCI dSGf GdOjf Hf GdNWjH s
(3GfXQ Qbe (B1289 (3JGQjNs
(3fSNI SGOSIs
(3hGdehLhO efg KdGKI bWY GdbWYI GdChdi JHOC HGdHGH GdSGOS ef GdbSe GdChd aj PcQ HYV GdhGaOjf Ydi GdCfOdS ef Cgd GdeTQb hJfJgj HBNQ GdHGH GdKGfj ef GdbSe GdKGfjs
(3h gh GdNGU HfTGAI dSGf GdOjf Hf GdNWjH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B78s
Keywords: (3GdJGQjNs